Is India too poor to be green? - Temper, Leah; Martinez-Alier, Joan (2007)
The argument that the best way for a growing economy to treat environmental problems is to get rich first and clean up the mess later is not defensible. India cannot replicate the processes of the developed west because it can neither shift environmentally damaging activities abroad nor can it "export" surplus labour relreased from agriculture to Europe or the US. - Reproduced.
Keywords: Environment - India; Environment